Enhanced Rhodococcus pyridinivorans HR-1 anode performance by adding trehalose lipid in microbial fuel cell. (November 2018) - Cheng, Peng; Shan, Rui; Yuan, Hao-Ran; Deng, Li-fang; Chen, Yong
Highlights: Current density and power output were promoted by the addition of bio-surfactant. MFC internal resistance was reduced with the treatment of trehalose lipid. Cyclic voltammetry and electrochemical impedance spectroscopy were investigated. Abstract: In this study, a trehalose lipid was added to a Rhodococcus pyridinivorans -inoculated MFC to improve the power output by enhancing electron transfer. Upon trehalose lipid additions of different concentrate from 0 to 20 mg/L, the maximum power density increased from 54.7 mW/m 2 to 324.4 mW/m 2 (5.93 times) while the corresponding current density was 3.66 times increased from 0.35 A/m 2 to 1.28 A/m 2 . Cyclic voltammetry analysis revealed that the addition of trehalose lipid increased the electron transfer performance, while electrochemical impedance spectroscopy results proved a decrease in internal resistance. It was demonstrated that adding bio-surfactant in MFC was a novel way to enhance power output performance.